Adherence to gynecological screening impacted by experienced orthodontic treatment in childhood - Schott, Sarah; Rippinger, Nathalie; Bruckner, Thomas; Brucker, Janina; Dinkic, Christine; Rom, Joachim; Sohn, Christof (Archives of gynecology and obstetrics, 2019)
BackgroundDental and cervical controls are two established screening programs in Germany. Compliance to orthodontic treatment in childhood is essential for dental health and one of the first health interventions that requires adherent behavior; therefore, it may be associated with participation in further screening programs in adulthood. However, it is not yet known whether early orthodontic treatment influences long-term screening adherence.MethodsUsing a questionnaire administered during a visit to a special dysplasia outpatient service, this case-control study evaluated women’s personal history of orthodontic care, long-term satisfaction, and dental and gynecological screening adherence. Oral health status and dental anxiety were assessed with validated instruments. Cases were categorized as cervical dysplasia only (S2) or cervical dysplasia with conization (S1) and compared to healthy controls with a normal PAP smear.ResultsA study population of 233 participants included 132 cases and 101 controls. The control group had had orthodontic treatment during childhood more often than our study population with abnormal PAP smears (68.3% controls versus 56.1% subjects; p < 0.005). Orthodontic treatment was not associated with attending dental appointment or gynecological check-ups. However, women with an orthodontic treatment in childhood were significantly more often vaccinated against human papillomavirus than women without orthodontic treatment (p < 0.03).ConclusionData suggest that women with orthodontic treatment in childhood are more conscious about prevention strategies in adulthood; therefore, compliant behavior might be established in childhood.
Published online: 30 October 2018
Gesehen am 25.07.2019